Bright English Textbook Development for Primary School Grade 6 in Batu City - Erlyna Abidasari; Kharisma Naidi Warnandha Sabgini; Nina Inayati (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
Based on Indonesia’s current curriculum, English is no longer compulsory for primary school subject; it is only required to be taught starting at the secondary school level. However, in Batu city, the local government treats English as compulsory local content subject for their area development, which certainly raises several challenges for English teachers in Batu due to the lack of supplementary books and other supporting activities. Since 2019, the supplementary book writing project has been initiated, however, the draft still needs to be evaluated before being published, and this is the focus of this project. The study was projected to describe the development process of the Bright English textbook. This study employed a descriptive-analytical approach, involving primary school teachers, students, and an expert. Questionnaires were distributed to teachers and students to evaluate the overall display and content of the book, whereas an evaluation sheet was delivered to the expert to rate the language level and content. Adapting Richards (2001)’s material development theory, three stages of development were present; training, implementation, and evaluation-publication. The training stage facilitated teachers to better comprehend the textbook structures and varied activities relevant to Batu's wisdom and values, while the implementation stage encouraged more interactive and fun collaborative learning plans through synchronous offline and online meetings. The evaluation and publication phase perfected the textbook in various aspects such as its layout, font style selection, picture, instructions, number of pages, language mechanics, uniformity of graphic design, and placement inconsistency.